A tutela preventiva da responsabilidade civil - Saraiva, David Emanuel Chiquita (2015)
The contemporary society is characterized by high risks. Today, the prevention of damages is as important as compensation. This is due to the fact that the potentiality of several damages is not in line with compensation, because often compensation proves to be impossible. Civil law should be at the service of the citizens, which explains that the heart of the institution of non-contractual liability has gradually moved towards the victim's protection. It is requested from Tort law an active attitude that seeks to avoid damages, reducing its dimension and frequency. The imputation by risk proves to be necessary and useful in the present context as it demonstrates the ability to model behaviors, functioning as a warning for agents engaged in hazardous activities. Economically, it seeks to prevent socially inefficient behaviors. Strict liability assumes notorious importance as a deterrent and in the dispersion of damage by society. The paradigm of the imputation founded on fault has proved insufficient for the effective protection of the interests of the citizens, particularly if based in an anachronistic vision of the concept of fault. Prevention arises in several areas, especially in environmental liability, producer liability and liability based on infringement of copyright and rights relating to the personality. To overcome the damage as the gauge for compensation does not inevitably mean the recognition of the punitive approach. Prevention should not be confused with reactive/punitive objectives. The deterrence of unlawful conduct is not subordinated to punishment.